Discovery learning untuk meningkatkan aktivitas belajar siswa - Almali Nurul Putri; Wa Ode Lili Andriani Nasri; Dian Renata (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
learning activities were one of the important factors that need to be developed in learning. In fact, there were still students who have low learning activities. One of the efforts that can be done is through discovery learning. The aimed of this study was to determine whether discovery learning can improve student learning activities. This research was a classroom action research which consists of two cycles. The subjects in this study were students of class X Otomatisasi Tata Kelola Perkantoran with a total of 47 students. The data in this study were collected using observation and questionnaire techniques. The data were analyzed qualitatively and to test the hypothesis used t test with the help of Statistical Product for Service Solution version 20. The results showed that there was an increase in student learning activities through discovery learning.